DEGRADATION OF THE COMPRESSIVE STRENGTH OF UNSTIFFENED/STIFFENED STEEL PLATES DUE TO BOTH-SIDES RANDOMLY DISTRIBUTED CORROSION WASTAGE - NOURI, ZORAREH HADJ MOHAMMAD ESMAEIL (2010)
THE PAPER ADDRESSES THE PROBLEM OF THE INFLUENCE OF RANDOMLY DISTRIBUTED CORROSION WASTAGE ON THE COLLAPSE STRENGTH AND BEHAVIOUR OF UNSTIFFENED/STIFFENED STEEL PLATES IN LONGITUDINAL COMPRESSION. A SERIES OF ELASTIC-PLASTIC LARGE DEFLECTION FINITE ELEMENT ANALYSES IS PERFORMED ON BOTH-SIDES RANDOMLY CORRODED STEEL PLATES AND STIFFENED PLATES. THE EFFECTS OF GENERAL CORROSION ARE INTRODUCED INTO THE FINITE ELEMENT MODELS USING A NOVEL RANDOM THICKNESS SURFACE MODEL. BUCKLING STRENGTH, POST-BUCKLING BEHAVIOUR, ULTIMATE STRENGTH AND POST-ULTIMATE BEHAVIOUR OF THE MODELS ARE INVESTIGATED AS RESULTS OF BOTH-SIDES RANDOM CORROSION.